Methods of increasing the technical and tactical preparation of badminton players during the training process - Boltayevna, M. S. (Central Asien Journal Social Sciences and History, 2023)
Technical and tactical training is to conduct the game to win, taking into account the real capabilities of the main game qualities of the athletes (stability, accuracy, endurance, mental stability, etc.), from the dimensions of the field, equipment, is a general plan for effective use of yin techniques and tactics.